2019
DOI: 10.1210/clinem/dgz092
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Reduction Rate After Saline Infusion Test May Be a Novel Prediction in Patients With Primary Aldosteronism

Abstract: Objective Accurate assessment and localization of aldosterone-producing adenomas (APAs) are essential for the treatment of primary aldosteronism (PA). Although adrenal venous sampling (AVS) is the standard method of reference for subtype diagnosis in PA, controversy exists concerning the criteria for its interpretation. This study aims to determine better indicators that can reliably predict subtypes of PA. Method Retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 28 publications
4
25
0
12
Order By: Relevance
“…On the other hand, PAC reduction rate in SIT was significantly lower in patients with unilateral hypersecretion. Recently, Nagano et al demonstrated that the combination of PAC reduction rate in SIT and PAC after SIT is a useful criterion for discriminating unilateral hypersecretion from bilateral hypersecretion, 37 which is consistent with our study. Although not only our study but their study did not purely compare the diagnostic significance of each value after confirmatory tests and the value changes in the confirmatory tests, in our study, the PAC value after CCT or SIT tends to be superior to the value change of PAC in SIT.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, PAC reduction rate in SIT was significantly lower in patients with unilateral hypersecretion. Recently, Nagano et al demonstrated that the combination of PAC reduction rate in SIT and PAC after SIT is a useful criterion for discriminating unilateral hypersecretion from bilateral hypersecretion, 37 which is consistent with our study. Although not only our study but their study did not purely compare the diagnostic significance of each value after confirmatory tests and the value changes in the confirmatory tests, in our study, the PAC value after CCT or SIT tends to be superior to the value change of PAC in SIT.…”
Section: Discussionsupporting
confidence: 92%
“…Auf der anderen Seite fanden modifizierte Kriterien von Bestätigungstests auch Verwendung in der Subtypdifferenzierung. Verschiedene Studien konnten zeigen, dass anhand des Ergebnisses des Kochsalzbelastungstests mittels eines Scores eine Subtypdifferenzierung möglich ist [19,20]. Kürzlich konnten Burello und Mitarbeitende in einer großen Studie mittels "Machine Learning" Vorhersagemodelle für die PHA-Subtypdiagnostik validieren [21].…”
Section: Merkeunclassified
“…Based on the analysis of the receiver operating characteristic curve, they proposed an optimal cut-off value of PAC after seated saline infusion as 13.1 ng/dL for subtype prediction, which had a sensitivity of 0.94 and a specificity of 0.79 for unilateral PA [ 137 ]. Subsequently, Nagano et al also examined SIT-based subtype prediction, showing the potential of PAC reduction rate after saline infusion [ 138 ]. Using 209 PA cases, they demonstrated that an actual PAC less than 8.79 ng/dL after saline infusion at supine position had a sensitivity and a specificity of 0.80 and 0.86, respectively, for BHA detection, while over 33.8% PAC reduction between before and after SIT had a higher sensitivity of 0.87 [ 138 ].…”
Section: Recent Advance In Simplifying the Pa Diagnostic Flowmentioning
confidence: 99%
“…Subsequently, Nagano et al also examined SIT-based subtype prediction, showing the potential of PAC reduction rate after saline infusion [ 138 ]. Using 209 PA cases, they demonstrated that an actual PAC less than 8.79 ng/dL after saline infusion at supine position had a sensitivity and a specificity of 0.80 and 0.86, respectively, for BHA detection, while over 33.8% PAC reduction between before and after SIT had a higher sensitivity of 0.87 [ 138 ]. Similarly, Hashimura et al built a prediction score using both baseline PAC and ARR reduction in SIT with a high specificity of 0.97 for distinguishing BHA, allowing 49% of the cases to circumvent AVS [ 139 ].…”
Section: Recent Advance In Simplifying the Pa Diagnostic Flowmentioning
confidence: 99%
See 1 more Smart Citation